MMC Materials Ultrasonic Machining and its Economic Aspects. (2016) - Líska, János; Kun, Krisztián; Líska, Katalin
Abstract: Today, special materials are used at more and more places. These materials generally are characterized by excellent mechanical properties. The aluminium foam is one type of special material. This material can be characterized by ultra-light weight and very high strength. Moreover, this material has very good vibration absorbing capability due to the cellular structure. Nowadays, these materials are used not only in the building industry, but also in vehicle and aircraft industry started to use them. Milling is necessary for becoming to be installed. Due to the metal-ceramic components, milling of these materials is able only with special equipments. Since the aluminium tends to smear (during the milling), therefore the same situation is at aluminium foams. The cell structure even increases this phenomenon. Therefore, deburring appears as separate cost, during the milling process (next to machine cost). Is known a lot of deburring technologies, in order to select the right technology we need to know theoretical basics and the size of expected costs of deburring technologies. The aim of our research is to investigate the possibilities of machinability of aluminum foam with help of ultrasonic technology (how to machining economically without burrs).